Sosialisasi Tindakan Pencegahan Kondisi Kritis Stroke - Riani, Riani; Rinancy, Hariet; Intan, Intan (Institut Teknologi Pendidikan Indonesia, 2024)
Stroke is the number one cause of disability and the second cause of death in the world after heart disease. Preventive measures in the form of prehospital treatment need to be emphasized. This is important to ensure an improvement in the quality of life of stroke sufferers in addition to more effective management to reduce the incidence of stroke. Primary prevention of stroke includes efforts to improve life and control various risk factors. This effort is aimed at healthy people and high-risk groups who have never had a stroke. The problem that arises here is that Mr. S's partner/family does not know 1) the conditions that pose a risk of a critical condition in a person who experiences a stroke, the family/ Mr. S does not know what things can prevent a person with a stroke from becoming critical. 2) Mr.S stated that his blood pressure was 210/100 mmHg and his cholesterol level was 324 mg/dL which tended to increase because he was not disciplined in consuming and managing his food intake and Mr.S was also an active smoker. The worsening condition of patients after a stroke causes a decrease in the function of the movement organs, which causes disruption in the performance of daily activities in patients, which can lead to total dependence on other people to fulfill the needs of daily activities. Stroke must receive serious attention if you experience a critical condition, because it can cause brain damage and even the death of brain cells in a matter of minutes. Information related to critical stroke conditions is expected to help patients prevent and provide assistance in situations that threaten death.